Mass education materials published in the early period of People's Republic of China, 1949-1952 - Hunter, Edward, 1902- (1949)
The collection includes picture books, songs published in Shanghai, Beijing, etc. during 1949-1952, educating people to understand that PLA is People's army. They are not published by government agencies. Some include manuscript translation in English.